Practical aspects of usage of insulin in India: Descriptive review and key recommendations. Issue 3 (May 2021) - Mukherjee, Jagat Jyoti; Rajput, Rajesh; Majumdar, Sujoy; Saboo, Banshi; Chatterjee, Sanjay
Abstract: Background and aims: Insulin therapy is an integral part of diabetes management. However, reliable and easily accessible information on a number of basic facts concerning insulin therapy, including storage of insulin, managing insulin therapy during travel, nuances of insulin use while driving, and dose adjustments during sick days is lacking. This document aims to make readily available, reliable, and easy to implement information on these essential but relatively less discussed aspects of insulin therapy. Method: Literature search was performed using PubMed and Cochrane Library from inception till 1 st of July 2019. The relevant topics were reviewed by a panel of 5 specialists and 23 contributing physicians and endocrinologists, who had assembled at Bengaluru, India for the 13th National Insulin Summit. After a thorough review of the literature, and following detailed discussions, the committee arrived at these recommendations. Results: Unopened vials and cartridges of insulin should be stored at 2 °C–8 °C in a refrigerator and protected from direct sunlight. For opened vials and in-use cartridges, manufacturer's instructions must be followed at all times. While traveling by air, dose adjustments are required only when flying across more than five time zones in the east or west directions. Insulin therapy should not be omitted or stopped during an acute illness; rather the doses need careful adjustments based on self-monitoring of blood glucose. Conclusion: Recommendations and guidelines, covering many common aspects of insulin therapy are readily available. This consensus document aims to make recommendations for those essential aspects of insulin therapy that are crucial for its success but are relatively less known and less discussed. Highlights: Avoid storing insulin in the door of a refrigerator as it is prone to temperature fluctuations. In the absence of a refrigerator, insulin vial can be stored in a cool wet cloth. Patients should not discontinue insulin during an acute illness or infection. Patients should not miss insulin doses or substitute with an OAD while traveling. Professional drivers should always keep in reach emergency supply of sugar sachets, chocolates.